Anxiety And Depression Among Medical Students During Covid-19 Pandemic In Faisalabad - Din, Mohi ud; Naveed, Hafiz Usama; Tauseef, Maryam; Javed, Maham; Sarfraz, Sana; Waheed, Jahanzaib (Journal of Rawalpindi Medical College, 2023)
Objectives: To find out the frequency of anxiety and depression among medical students during the Covid-19 pandemic and to study their relationship with socio-demographic factors. Methodology: Analytical cross-sectional study was conducted on medical students of various medical institutions in Faisalabad and their consent was taken beforehand. The study duration was 2 months (August to September 2021). Ethical approval was taken. The questionnaire was distributed online through google forms on social media platforms to all MBBS students of a medical college and the total number of responses received was 452. Non-probability purposive sampling was done. The inclusion criteria were those students who gave consent and filled out the questionnaire and the exclusion criteria were those who didn’t concede. A validated and structured questionnaire was used. The questionnaire consisted of four sections: demographic data; COVID-19-related attitudes and practising preventive behaviours, generalized anxiety disorder scale – 7 (GAD-7) to determine anxiety among medical students and patient health questionnaire – 9 (PHQ-9) to determine depression. Results: Most of the students i.e. 132 (29.2) were having mild anxiety, followed by minimal, moderate and severe anxiety. Similar scores were observed in PHQ-9 results which showed mostly students were having mild depression i.e. 127 (28.1) followed by minimal, moderate, moderately severe and severe depression respectively. Average GAD-7 score was 8.73 (M = 8.73; SD = 5.78); average PHQ-9 score was 10.78 (M = 10; SD = 7.1). Significant relationship was found between gender (p = 0.00), year of study (p = 0.039), suffered Covid-19 in present or past (p = 0.00), afraid of getting Covid-19 (p=0.001) with anxiety and gender (p = 0.00), suffered Covid-19 in present or past (p=0.001) and afraid of getting Covid-19 infection (p=0.001) with depression. Conclusion: There was a high prevalence of medical students suffering from anxiety and depression during Covid-19. The students in the age group above 21 years, females, year of study (4th year) and afraid of getting Covid-19 infection were at higher risk of psychological distress in a pandemic. It is important to find ways to alleviate the pressure and fear of college students, provide them with more social support, and help them adapt to the changes in their learning styles and lifestyle.